Building a Corpus of Oral Testimonies of the Holocaust: a case study in corpus linguistics and oral history - Wilson, C (2023)
This dissertation will give an overview of what goes into creating a digital cross- linguistic corpus. Using a case study, I will describe the elements, methodology, and possible research outcomes of building a digital corpus. The case study con- sists of a collection of oral testimonies of Holocaust survivors that have been tran- scribed into a collection of English, Polish, Russian, Czech, and Hungarian texts. Building on existing literature, this dissertation will describe how corpus linguis- tics can make research data more accessible to researchers of many different areas of scholarship. Having given an overview of how a corpus is created and digi- tally distributed, including the range of tools and platforms available for analysing corpora, I will explore two areas of possible research within corpus linguistics: geo-location using named entity recognition programmes, and syntactic analysis of hedging used in oral histories thanks to part of speech tagging. Through build- ing a corpus of Holocaust Oral Testimonies, I hope to demonstrate how digital methods of corpus linguistics can help further interdisciplinary research within the digital humanities.